Cross-School Coordination and Its Influence on Team Performance in Islamic Integrated Junior High Schools of the Riau Islands Province - Taufik; Suaidi; Rusmini (International Journal of Post Axial: Futuristic Teaching and Learning, 2026)
This study examines the influence of cross-school coordination on team performance within Islamic Integrated Junior High Schools in the Riau Islands Province. Using a qualitative case study approach, the research explores how collaborative mechanisms, shared leadership practices, and inter-school communication contribute to managerial effectiveness and organizational stability. Findings indicate that structured coordination activities enhance strategic decision-making, strengthen professional competence, and foster a coherent institutional culture. Cross-school collaboration also supports the development of shared norms, improves the accuracy of performance evaluation, and increases operational efficiency through streamlined administrative processes. These interactions create a supportive environment that enables leaders to address challenges more responsively while encouraging innovation and accountability. Overall, cross-school coordination plays a pivotal role in elevating team performance and strengthening institutional capacity across Islamic Integrated educational settings.